THE INFLUENCE OF SOCIAL INFLUENCE AND PEER INFLUENCE ON INTENTION TO PURCHASE IN E-COMMERCE - Gunawan, Celine Miyuki; Rahmania, Laili; Kenang, Irantha Hendrika (Review of Management and Entrepreneurship, 2023)
The development of information technology increases the number of active users of mobile phones and several platforms in it, such as ecommerce. Social groups and peers influence determining consumer behavior to make purchasing decisions on e-commerce. The purpose of this study was to determine the effect of social influence and peer influence on the intention to purchase on e-commerce which is supported by the theory of TPB (Theory of Planned Behavior) and TAM (Technology Acceptance Model). The data in the study were obtained from 338 students in Surabaya who had shopped through e-commerce. This study uses Confirmatory Factor Analysis to determine the validity and reliability of the construct and Partial Least Square in testing the relationship between the variables. The results of the analysis have proven that social influence and peer influence variables have a significant influence on attitudes towards using e-commerce and intention to purchase. Social and peer influence can influence behavior in making purchasing decisions among consumers, especially teenagers through trust, interaction, habits, recommendations, and information provided. This research is expected to provide knowledge to sellers in e-commerce for the development of marketing their products and services in the future.